Similarities and Differences in the Perception of Atopic Dermatitis Burden Between Patients, Caregivers, and Independent Physicians (AD-GAP Survey) - Amy S. Paller; Stephan Weidinger; Korey Capozza; Andrew E. Pink; Mark Tang; Xavier Guillaume; Amy Praestgaard; Marjorie Leclerc; Chien-Chia Chuang; Ryan B. Thomas; Randy Prescilla (Adis, Springer Healthcare, 2023)
Abstract Introduction Atopic dermatitis (AD)-a chronic inflammatory skin disease characterized by intense itching-can have a detrimental impact on quality of life (QoL). We report results of a quantitative assessment of pediatric patient, caregiver, and physician perceptions of AD burden in children and adolescents. Methods Pediatric patients (aged 6-11 [children] or 12-17 [adolescents] years) with moderate-to-severe AD, their caregivers, and independent physicians were recruited in 13 countries. Caregivers and their children/adolescents completed an online survey about the impact of AD on 16 key items of patient QoL. Physicians completed surveys on their patients aged 6-11 and 12-17 years. Best-worst scaling was used to rank the importance of the QoL items. Results Overall, 1447 children/adolescents with moderate-to-severe AD (aged 6-11 years: 701; 12-17 years: 746), 1447 caregivers, and 1092 physicians participated. Patients and caregivers in both age groups ranked disturbed sleep as the most important QoL item, followed by feeling ashamed because of AD. Independent physicians ranked feeling ashamed because of AD as the most important QoL item for both age groups, followed by disturbed sleep for those aged 6-11 years and being singled out for those aged 12-17 years. The relative importance of the 16 QoL items to patients was strongly aligned between patients in both age groups and their caregivers, but somewhat less so between patients and physicians. Between-country differences were more apparent in physician- versus patient-/caregiver-reported results. Conclusion The most burdensome QoL items were impact of AD on sleep and feeling ashamed. Caregivers and physicians correctly identified the QoL items most burdensome to patients. However, patient and caregiver perceptions were generally more closely aligned than patient and physician perceptions. Between-country differences in perceptions (particularly for physicians) were observed, probably due to multifactorial reasons, necessitating further evaluation. Video Abstract (MP4 42,877 kb) Infographic